Introduction of the New Technologies of Teaching into the School Practice - Nazarenko, Tetiana (Pedagogical Discourse, 2015)
This article highlights current issues related to the process of modern technology in geography teaching into the practice of school. The problems, arising from the methodological peculiarities of teachers with different educational and different format geographic information, have been analyzed. The guidelines as for the application of information technology of teaching geography, which form informational culture of the student, have been offered.